Cognitive Reevaluation of Outcomes in Response to Underpayment Inequity - Greenberg, Jerald (Academy of Management Journal, 1989)
A pay cut was theorized to create underpayment inequity among 114 salaried clerical workers. Relative to when their pay was subsequently reinstated, workers cognitively augmented the perceived importance of work environment features as contributors to their overall payment equity. These findings support equity theory's claim that cognitive distortion of outcomes may effectively redress perceived inequities.